2021
DOI: 10.3390/en14020415
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Wireless Power Transfer System Based on a Frequency Reconfigurable Microstrip Patch Antenna Array

Abstract: The microwave wireless power transfer (MWPT) technology has found a variety of applications in consumer electronics, medical implants and sensor networks. Here, instead of a magnetic resonant coupling wireless power transfer (MRCWPT) system, a novel MWPT system based on a frequency reconfigurable (covering the S-band and C-band) microstrip patch antenna array is proposed for the first time. By switching the bias voltage-dependent capacitance value of the varactor diode between the larger main microstrip patch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In [32], a novel Microwave power transfer (MWPT) system based on a frequency reconfigurable (covering the Sband and C-band) microstrip patch antenna array is proposed for the first time in place of a magnetic resonant coupling WPT system. The working frequency band of the MWPT system can be changed from the S-band to the C-band by changing the bias voltage-dependent capacitance value of the varactor diode between the main microstrip patch and the smaller side microstrip patch.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…In [32], a novel Microwave power transfer (MWPT) system based on a frequency reconfigurable (covering the Sband and C-band) microstrip patch antenna array is proposed for the first time in place of a magnetic resonant coupling WPT system. The working frequency band of the MWPT system can be changed from the S-band to the C-band by changing the bias voltage-dependent capacitance value of the varactor diode between the main microstrip patch and the smaller side microstrip patch.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…The main fields of research in UHV transmission for the global electric grid interconnections are: UHV AC/DC substations and circuit design [146,147]; electromagnetically controlled environmental systems [148]; project management, construction and handling guidelines of tests on UHV equipments [149,150]; development of standard for testing of equipments; gas insulated transmission lines [151,152]; unmanned aerial and robot inspecting vehicles [153]; HVDC power grid protection and control [154][155][156]; performance and design evaluation of wireless, super-conductive and pipe power transmission technology [157][158][159][160][161].…”
Section: Development Of Uhv Transmission Systemsmentioning
confidence: 99%
“…Wireless power transmission (WPT) is classified into radiative and non-radiative transmission. Nonradiative transmission can achieve high-efficiency transmission over short distances, whereas in radiative transmission, while there is the possibility of long-distance transmission, it is very difficult to improve the transmission efficiencies [1][2][3][4][5][6][7][8]. Yang has reported that the transmission efficiency of 46.9% with a distance of 100 cm can be obtained by using 8×8 array antennas for both transmitting and receiving [8].…”
Section: Introductionmentioning
confidence: 99%